Assessing stability of mine workings driven in stratified rock mass - Imashev, Askar; Suimbayeva, Aigerim; Zhunusbekova, Gaukhar; Adoko, Amoussou Coffi; Issakov, Bekzhan (Mining of Mineral Deposits, 2024)
Purpose.The research purpose is to assess the stability of mine workings driven in a stratified rock mass by studying the influence of the stratified rock bedding angle on the rock mass stress-strain state (SSS). Methods. The research uses both experimental and numerical methods. Experimental studies are carried out using rock samples with different angles of rock layer occurrence, while numerical modeling is performed using the RS2 (Geotechnical Finite Element Analysis) software based on the generalized Hoek-Brown failure criterion. The studies are carried out on models covering the border area of the mine workings driven in the mass with the angles of rock occurrence from 0 to 75°. Findings. Experimental and numerical studies have shown that when the rock layer inclination angle changes, significant changes occur in the stress concentration zones around the mine workings. An increased rock layer inclination angle is accompanied by a change in stress distribution, which is important for assessing the stability of mine workings. A particularly strong influence is observed at the angles of rock occurrence 30° and above. Originality. The research novelty is in revealing the patterns in the stress distribution in the stratified rock masses depen-ding on the rock layer inclination angle. Research results provide new data on the rock interaction mechanisms in difficult geological conditions. Practical implications. The results obtained can be used in the planning and operation of mine workings in difficult geological conditions. By taking into account the changes in stress zones caused by the rock layer inclination angle, it is possible to improve the safety and efficiency of mining operations.